Novel Anterior Brainstem Magnetic Resonance Imaging Findings in Non-Small Cell Lung Cancer with Leptomeningeal Carcinomatosis - Cheng, Chun-Yu; Hsu, Chia-Yu; Tsai, Yuan-Hsiung; Lin, Kuang-Lin; Huang, Cih-En; Fan, Yi-Hong; Chin, Shy-Chyi; Huang, Yen-Chu (Frontiers in Neurology, 2017)
Leptomeningeal carcinomatosis is found in around 4% of patients with non-small cell lung cancer. The most common radiological finding of leptomeningeal carcinomatosis is diffuse leptomeningeal enhancement on contrast-enhanced brain magnetic resonance imaging (MRI). Herein, we report a novel brain MRI finding — non-enhanced, band-like, symmetric restricted diffusion along the anterior surface of the brainstem — of leptomeningeal carcinomatosis in four patients with non-small cell lung cancer. We also identified three additional cases with similar MRI findings in a literature review. We hypothesized that the restricted diffusion along the anterior brainstem was caused by malignant cells concentrating in the cistern around the brainstem and infiltrating into the circumferential perforating arteries along the anterior brainstem surface, which then resulted in microinfarctions.